TOWARD A RIBA-FREE MACROECONOMIC PARADIGM: RECONSTRUCTING INFLATION DYNAMICS AND ECONOMIC EQUILIBRIUM - Farza Faremi Adirama (Hikmah: Journal of Islamic Studies, 2026)
AbstractThis study develops a conceptual and normative-analytical framework to reassess the role of interest-based monetary policy in managing inflation. Rather than employing econometric testing, the research adopts an integrative literature review methodology, drawing on macroeconomic theory, Islamic economic principles, and behavioural-strategic analysis. The literature selection is based on relevance to inflation dynamics, methodological contribution, and representation of both supportive and critical perspectives, covering recent studies (2015–2025) as well as foundational works in Islamic economics. Using thematic synthesis, the study identifies recurring patterns, contradictions, and gaps across the literature, particularly regarding the limitations of interest rate policy under supply-side shocks and behavioural instability. The findings indicate that inflation is better understood as a multidimensional phenomenon shaped by real-sector constraints, financial system structures, and strategic interaction among economic agents. Based on this synthesis, the article proposes a hybrid analytical framework consisting of three components: real-sector anchoring, riba-free financial mechanisms, and strategic behavioural alignment. The contribution of this study lies in explicitly bridging normative Islamic principles with empirical macroeconomic reasoning, offering a preliminary framework rather than a fully operational model. The findings should therefore be interpreted as conceptual propositions requiring further empirical validation. AbstrakStudi ini mengembangkan suatu kerangka konseptual dan normatif-analitis untuk menilai kembali peran kebijakan moneter berbasis suku bunga dalam mengelola inflasi. Alih-alih menggunakan pengujian ekonometrik, penelitian ini mengadopsi metode tinjauan literatur integratif dengan mengacu pada teori makroekonomi, prinsip ekonomi Islam, serta analisis perilaku dan interaksi strategis. Pemilihan literatur didasarkan pada relevansi terhadap dinamika inflasi, kontribusi metodologis, serta representasi perspektif yang mendukung maupun yang kritis, mencakup studi-studi terbaru (2015–2025) serta karya-karya fundamental dalam ekonomi Islam. Melalui pendekatan sintesis tematik, penelitian ini mengidentifikasi pola berulang, kontradiksi, dan kesenjangan dalam literatur, khususnya terkait keterbatasan kebijakan suku bunga dalam menghadapi guncangan sisi penawaran dan ketidakstabilan perilaku. Temuan menunjukkan bahwa inflasi lebih tepat dipahami sebagai fenomena multidimensional yang dibentuk oleh keterbatasan sektor riil, struktur sistem keuangan, serta interaksi strategis antar pelaku ekonomi. Berdasarkan sintesis tersebut, artikel ini mengusulkan suatu kerangka analitis hibrida yang terdiri atas tiga komponen: penguatan sektor riil (real-sector anchoring), mekanisme keuangan bebas riba, dan penyelarasan perilaku strategis. Kontribusi utama studi ini terletak pada upaya menjembatani secara eksplisit prinsip-prinsip normatif Islam dengan penalaran empiris makroekonomi, dengan menawarkan kerangka awal yang bersifat konseptual, bukan model operasional yang telah teruji. Oleh karena itu, temuan dalam penelitian ini sebaiknya dipahami sebagai proposisi konseptual yang masih memerlukan validasi empiris lebih lanjut.